ANALYSIS OF CONSUMER ATTITUDES AND PREFERENCES TO BANANA PURCHASE DECISIONS IN THE TRADITIONAL MARKET OF SEMARANG CITY - Ewin Rumapea; Wiludjeng Roessali; Edy Prasetyo (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
Banana is one type of fruit that is in great demand by the Indonesian. The number of banana varieties circulating in fruit retailers will affect consumer behavior in making purchasing decisions. This study aimed to identify the number of types of bananas that consumers buy the most, analyze consumer attitudes towards the most considered attributes in purchasing decisions, and analyze consumer preferences for banana attributes in traditional markets in Semarang City. The method used in this research is a survey. Determination of the sample is done by quota sampling with a total sample of 108 respondents. Methods of collecting data through interviews with the help of a questionnaire. Data were analyzed descriptively, with Multi-attribute Fishbein attitude analysis and Conjoint analysis. The results showed that the type of banana consumers bought the most was the Kepok anana with a percentage of 45%, while the banana that was rarely purchased was the Mas banana with a rate of 6%. Consumer attitudes towards the attributes that are considered in the decision to buy bananas are the taste attributes (17.17) are positive, fruit skin color (14.97) is neutral, size (10.46) is negative, and the number of fruits per comb (9.95) is negative. Consumer preferences are indicated by the most prioritized importance value, namely bananas with a slightly sweet taste, greenish-yellow skin color, a large number of fruits per comb (>16 pieces), and medium-size (10-14cm).